2020
DOI: 10.1101/2020.02.09.940353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aesthetic preference for art emerges from a weighted integration over hierarchically structured visual features in the brain

Abstract: It is an open question whether preferences for visual art can be lawfully predicted from the basic constituent elements of a visual image. Moreover, little is known about how such preferences are actually constructed in the brain. Here we developed and tested a computational framework to gain an understanding of how the human brain constructs aesthetic value. We show that it is possible to explain human preferences for a piece of art based on an analysis of features present in the image. This was achieved by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…While we agree, we suggest that linearity is a suitable starting point. Recent work comparing a linear rule versus a deep neural network to predict subjective aesthetic value found that both fared comparably (Iigaya et al, 2020). We argue that this also applies for our theoretical framework for aesthetic learning.…”
Section: Limitations and Outlooksupporting
confidence: 57%
See 1 more Smart Citation
“…While we agree, we suggest that linearity is a suitable starting point. Recent work comparing a linear rule versus a deep neural network to predict subjective aesthetic value found that both fared comparably (Iigaya et al, 2020). We argue that this also applies for our theoretical framework for aesthetic learning.…”
Section: Limitations and Outlooksupporting
confidence: 57%
“…Instead, we chose to limit the complexity of our theoretical framework at this first iteration to serve as a basic building block on which to incorporate the aforementioned factors. However, even a model based on low-level features can still be highly informative on aesthetic preferences of individuals, as recently demonstrated by Iigaya et al (2020). Additionally, a reinforcement learning circuit is easily amenable to additional factors, for example Leong et al incorporate attention directly into the reinforcement-learning circuitry computing subjective value, as we did with motivation (Leong et al, 2017).…”
Section: Limitations and Outlookmentioning
confidence: 81%
“…Visual and psychological processes related to art perception and processing have been proposed previously (Ramachandran and Hirstein, 1999;Leder et al, 2004), and neuroscientific studies assessed and localized brain activity in relation to esthetic value (Cela-Conde et al, 2004;Kawabata and Zeki, 2004;Vartanian and Skov, 2014;Lebreton et al, 2015). While esthetic value is considerably subjective, a recent study shows that (visual) esthetic value can be predicted by brain activity based on the integration and different weighing of (visual) features of the presented art image (Iigaya et al, 2020), including low-level (hue, saturation, lightness, color, brightness, blurring effects, edge detecting) (Li and Chen, 2009) and high-level features (color temperature, depth, abstract, emotion, complexity) (Chatterjee et al, 2010). Thus, presumably, primary and secondary rewards are not "randomly" processed in the brain but have -at least to a certain extent -a common ground in human brain computations of stimulus features, which have most likely evolved to serve adaptive behaviors in different environments (Skov and Nadal, 2018;Skov and Skov, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Others showed that fat and carbohydrate content elicit a supra-additive response for food valuation in the ventral striatum independent of liking (DiFeliceantonio et al, 2018), further highlighting that the brain's reward evaluation for food involve nutrient sensors in the gut (De Araujo et al, 2020). Considering art evaluation, a recent preprint suggests that feature integration of artistic stimuli might be ordered in an hierarchical way from visual processing up to the integration from low-and high-level image features in the brain, in particular in higher-order areas such as parietal and prefrontal cortex (Iigaya et al, 2020). While it might seem counterintuitive to want art similar to wanting food, it has been argued that art objects, such as prints of art paintings or photographs, are often object of desire, not only of art collectors (Berridge and Kringelbach, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation